Thrifting Practices Among Young People In Legi Market Jatinom Klaten - Iwan Fathoni; Nurhadi; Dwi Astutik (Jurnal Niara, 2024)
This research examines a phenomenon developing among young people regarding shopping for imported used clothing or what is often referred to as thrifting. This research aims to analyze the essence and meaning of thrifting practices carried out by young people in Pasar Legi Jatinom Klaten. The research method used is qualitative, using an ethnographic research approach. The selection of informants was done by using a purposive technique. Meanwhile, this study used three data collection techniques: observation, interviews, and documentation. The data analysis technique used Creswell's ethnographic analysis technique. This research uses Jean Baudrillard's theory of consumerism. The results of the research show that the practice of thrifting is not only an activity of buying and consuming imported used clothes, but more than that, the practice of thrifting has its meaning for young people, whereas thrifting has meaning as a series of complex processes related to clothing. In the practice of thrifting, consumers do not only wear imported second-hand clothes that they buy based on functional value, but more than that, the consumption of imported second-hand clothes by young people when thrifting is also determined by a set of desires for status, respect, prestige, and identity construction through a "marking mechanism."